KOMUNIKASI PEMASARAN PARIWISATA DI KABUPATEN LAHAT - Santhi Zinaida, Rahma; Adinda Merlthon’s Poetri, Dhea (JIKE : Jurnal Ilmu Komunikasi Efek, 2023)
Marketing communication is one of the factors that greatly affects the number of visitors to a website because it is a design how to attract visitors in various ways, so that visitors know and are interested in visiting the website. This study aims to find out how tourism marketing communication in Lahat districs is through the website www.panoramicoflahat.com. This study uses qualitative research methods with descriptive methods, data collection techniques using interviews and observations. The results of this study are, 1) Promotions carried out by the website www.panoramicoflahat.com, namely through social media Instagram and Facebook. As well as cooperating with various news media. However, the promotion is still not optimal. 2) The efforts of the website www.panoramicoflahat.com in presenting information to satisfy the curiosity of visitors, namely by choosing words that are easy to understand and determining interesting titles. 3) In addition to providing tourist information in Lahat districs, the website www.panoramicoflahat.com also provides services